The research of free aminoacids of water-soluble protein-polysaccharide complex of oyster mushroom pleurotus ostreatus - Varinsky, Boris; Kucherenko, Nataliia; Kolpakova, Olga (ScienceRise: Pharmaceutical Science, 2018)
Recently, the share of medicinal products of natural origin has increased in the pharmaceutical market of Ukraine. This is due to the fact that the pharmacological effect of natural substances provides a complex of biologically active substances, which has a high therapeutic effect and the minimum number of adverse reactions. Therefore, the study of chemical composition and standardization of natural substances is an important stage in pharmaceutical research. A promising source of active ingredients is the mushroom Pleurotus ostreatus. The chemical composition of this fungus is represented by a large number of biologically active substances, which ensures its many-sided use in folk medicine. Aim. The determination of qualitative and quantitative composition of free amino acids in the composition of water-soluble protein-polysaccharide complex (WPPSC) of oyster mushroom Pleurotus ostreatus was the aim of research. Methods. Physicochemical methods are the most commonly used to study active substances of natural origin. This is due to the fact that they provide high informative, accurate, efficient and reproducible. The method of high performance liquid chromatography (HPLC) was used to analyze the amino acid composition of the WPPSC of oyster mushroom Pleurotus ostreatus. This method is based on the separation of individual components due to different adsorption capacity. Results. Research of the amino acid composition of the WPPSC of oyster mushroom Pleurotus ostreatus showed that the complex contains 10 (7 %) free amino acids, among which 5 are essential. The detected aminoacids are aliphatic, heterocyclic and aromatic compounds. They are presented by glycine, alanine, leucine, isoleucine, threonine, selinum, lysine, arginine, histidine and phenylalanine. Conclusion. The qualitative and quantitative composition of the free amino acids of the WPPSC of oyster mushroom Pleurotus ostreatus was established. The method of determination and separation of free amino acids by the method of high-performance liquid chromatography is proposed. The obtained results are proposed for standardization of the initial substance in the process of production of medicines based on WPPSC of oyster mushroom Pleurotus ostreatus